2022
DOI: 10.3390/su14042045
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Research on Technological, Pedagogical, Didactical, and Social Competencies of Preservice TCFL Teachers

Abstract: With the development of China, learning the Chinese language has received more and more attention from international students. Teaching Chinese as a foreign language (TCFL) is crucial for spreading Chinese culture and promoting cultural exchanges. In recent years it has become the focus of attention of many scholars, and the heterogeneous cultural backgrounds and diverse language needs of learners determine that TCFL should promote the development of students’ intercultural communication competence in language… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
14
0
Order By: Relevance
“…Forecasts project exponential growth in the adoption of smart classrooms for the coming years (Uskov et al, 2015) due to the emergence of smart systems, applications and technologies that provide unprecedented opportunities for quality teaching and learning (Oubibi et al, 2022). In addition, there are credible signs that smart classrooms have the potential to revolutionize schooling.…”
Section: Quality For Smart Classrooms: a Socio-technological Perspectivementioning
confidence: 99%
“…Forecasts project exponential growth in the adoption of smart classrooms for the coming years (Uskov et al, 2015) due to the emergence of smart systems, applications and technologies that provide unprecedented opportunities for quality teaching and learning (Oubibi et al, 2022). In addition, there are credible signs that smart classrooms have the potential to revolutionize schooling.…”
Section: Quality For Smart Classrooms: a Socio-technological Perspectivementioning
confidence: 99%
“…They asserted that boys and girls use technology and related skills in different ways. Oubibi et al (2022) conducted research at a large university in Canada to determine whether college students of different genders use technology differently. They wanted to help us better understanding of gender’s role in technology adoption in post-secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…They wanted to help us better understanding of gender’s role in technology adoption in post-secondary education. They found that men and women approach technology differently, especially in terms of learning using software packages and computers ( Oubibi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of online teaching and learning has resulted in teachers’ stress and anxiety, especially for those with low ICT competence. 26 Apart from competence, studies have also reported teachers’ lack of willingness to shift from traditional face-to-face to distance (online) teaching and learning. 2 The UNESCO survey indicated that only half of the surveyed countries had offered additional training to teachers on distance education.…”
Section: Introductionmentioning
confidence: 99%